Evolution and dynamic properties of photospheric plasma in solar active regions (2017)
Abstract. This work has been done for the initiation of the author into the field of solar physics. The work is divided in two main blocks. The first part gives an overview of topics in solar physics taking a journey from the center of the Sun starting in the solar interior through different layers up to the solar atmosphere. The second part presents the computational tools used in this work as well as the development of several libraries created by the author for the international community of solar physics research. These routines were included into the packages for solar physics analysis (SunPy). Moreover, a sketch of the Local Correlation Tracking (LCT) technique is also outlined. A GUI application developed for preliminary analysis for the LCT algorithm is presented in the second part.The last two chapters of this block are focused on the study of horizontal and vertical flows in solar active regions. For this purpose, we used two datasets obtained and calibrated from the HMI (Heliographics Magnetogram Imager) - an instrument on board of the SDO (Solar Dynamics Observatory) spacecraft - that are continuum intensity maps and magnetograms in the line of sight (LOS). The following chapter describes the necessary pre-treatment procedure in order to obtain co-aligned datasets. For a proper temporal study, the so-called p-modes were removed applying a filtering routine. A local correlation tracking technique has been applied to obtain the horizontal and vertical flows of the selected regions. We compare the behavior of plasma flows measured in the continuum with the motion of magnetic structures. We found a strong relationship between the emergence of mesogranular cells, fast rising regions of plasma and the emergence of positive magnetic fields. In the last chapter, an observational analysis of active regions has been performed. The criterion used to select these sunspots is based on their umbrae lacking fully developed penumbra around them (partial penumbrae). The results indicate that in regions where there is no penumbra there is no radial outward flows, so-called moat flows, detectable around the sunspot.